TINJAUAN YURIDIS HAK PEMBELI KIOS HASIL KERJASAMA PEMBANGUNAN PASAR TRADISIONAL DENGAN SISTEM BUILD OPERATE AND TRANSFER (BOT) DI KABUPATEN BOGOR - Hidayat, Asep; Roestamy, Martin; Sihotang, Sudiman (DERECHTSSTAAT, 2017)
In realizing the general welfare, the acceleration in the construction sector more incentive. One of them is the development in the field of economy and trade, such as traditional markets. An integral part of the market is a kiosk which is a merchant selling. In implementing the needed development funds are not small so this should be a concern of government, given the limited funds of APBN / APBD. One alternative to overcome the limitations of these funds is through cooperation with the private sector with a system Build Operate and Transfer (BOT). Example analyzed is an agreement between the Government of Bogor Regency with PT. Fortunindo Artha Perkasa to revitalize Ciawi market in 2006. The aim of this study is to determine the actualization of the results of development cooperation agreements with the BOT system Ciawi market as well as to determine the legal certainty of ownership of a kiosk in a legal perspective objects. The method used in this research that the Juridical Sociological (Empirical), namely law as phenomena of society, as institutional, or behavior that develop. The technique of data collection is through a method Interview (interview) and Questionnaire Method. Based on the results of research conducted Writer that actualizing the result of cooperation with the BOT system between Bogor Regency with PT. Fortunindo Artha Perkasa is a mutually beneficial cooperation. The partnership is agreed in the contract that contains the rights and obligations of the parties. The agreement provides advantages, both for the Bogor Regency, PT. Fortunindo Artha Perkasa as well as for merchants. Concerning legal certainty, kiosks in law objects categorized as immovable property and have caused material rights to it, namely, the right material that gives pleasure and the right material that has the properties provide warranty. But, market stalls, if used as a credit guarantee of the legal protection for the debtor itself is weak because the market stall cannot be bound by the guarantee institution in Indonesia.